Digestibility of nutrients and energy in ingredients for bullfrogs during different phases of development - Mansano, C. F.M. [UNESP]; Macente, B. I. [UNESP]; Nascimento, T. M.T. [UNESP]; Pinto, D. F.H. [UNESP]; Pereira, M. M.; De Stéfani, M. V. [UNESP] (Hindawi, 2017)
The ability of frogs to digest dietary nutrients changes with growth, with the animals becoming more or less demanding. The objective of this study was to determine the apparent digestibility coefficients of protein, energy and ether extract of 14 ingredients used in bullfrog diets (spray-dried blood meal, hydrolysed feather meal, poultry by-product meal, red blood cell concentrate, tilapia by-product meal, sardine fishmeal, salmon fishmeal, meat and bone meal, corn gluten meal, soybean meal, corn, wheat bran, soy protein concentrate and soybean oil). A total of 2,325 bullfrogs (Lithobates catesbeianus) in different phases of development were used: early phase (mean weight of 30–50 g), growth phase (80–110 g) and finishing phase (150–200 g). Faeces were collected using the method of dissection. Marked differences in digestibility of the ingredients were observed between the different phases of frog development. Among the ingredients studied, salmon fishmeal and corn gluten meal showed good utilization of the protein (78.9% and 86.7%, respectively) and energy fraction (89.4% and 83.3%, respectively). The salmon fishmeal, poultry by-product meal, sardine fishmeal, soy protein concentrate, wheat bran and soybean oil exhibited good ether extract utilization (81.2%–92.8%), recommending their use in bullfrog diets.
Keywords: apparent digestibility coefficients; energy; ether extract; feeds; Lithobates catesbeianus; protein